A new Classification of Diabetic Nephropathy 2014: a report from Joint Committee on Diabetic Nephropathy. Issue 2 (March 2015) - Haneda, Masakazu; Utsunomiya, Kazunori; Koya, Daisuke; Babazono, Tetsuya; Moriya, Tatsumi; Makino, Hirofumi; Kimura, Kenjiro; Suzuki, Yoshiki; Wada, Takashi; Ogawa, Susumu; Inaba, Masaaki; Kanno, Yoshihiko; et al.
Abstract The Joint Committee on Diabetic Nephropathy has revised its Classification of Diabetic Nephropathy (Classification of Diabetic Nephropathy 2014) in line with the widespread use of key concepts, such as the estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD). In revising the Classification, the Committee carefully evaluated, as relevant to current revision, the report of a study conducted by the Research Group of Diabetic Nephropathy, Ministry of Health, Labor and Welfare of Japan. Major revisions to the Classification are summarized as follows: (i) eGFR is substituted for GFR in the Classification; (ii) the subdivisions A and B in stage 3 (overt nephropathy) have been reintegrated; (iii) stage 4 (kidney failure) has been redefined as a GFR <30 mL/min/1.73 m2, regardless of the extent of albuminuria; and (iv) stress has been placed on the differential diagnosis of diabetic nephropathy versus non‐diabetic kidney disease as being crucial in all stages of diabetic nephropathy.